Correlation between galectin-3, RDW, Hepc, HS and ferritin and prognosis of patients with acute onset of chronic heart failure - Lingling Yao; Yanjie Tan; Fei Chen (BMC Cardiovascular Disorders, 2022)
Abstract Background Chronic heart failure (CHF) is characterized by a high hospitalization rate and a high mortality rate. It is particularly important to identify biomarkers for predicting the prognosis of patients with acute attack of CHF. Purpose To observe the correlation between galectin-3, RDW, Hepc, HS and ferritin and the prognosis of patients with acute onset of CHF. Methods The study included 92 patients with acute onset of CHF who received treatment at our hospital between August 2020 and December 2021. After treatment, the patients were divided into the effective group and the non-effective group based on the effectiveness of treatment. The levels of galectin-3, RDW, Hepc, HS and ferritin before and after treatment were compared between the two groups and the correlation between prognosis of patients with acute attack of CHF and galectin-3, RDW, Hepc, HS and ferritin was observed. Results The effective rate was 71.74% (66/92) and the ineffective rate was 28.26% (26/92) in the 92 patients with acute attack of CHF in the study. Before and after treatment, the levels of galectin-3, RDW, Hepc, and HS were lower in the effective group than those of the non-effective group while the level of ferritin was higher in the effective group than that of the non-effective group (P < 0.05). Spearman correlation analysis showed that the level of prognosis of patients with acute attack of CHF was positively correlated with galectin-3, RDW, Hepc, and HS (r = 0.217, 0.109, 0.376, 0.765, P = 0.026, 0.032, 0.021, 0.006), and negatively correlated with ferritin (r = − 0.127, P = 0.037). The independent variables were galectin-3, RDW, Hepc, HS and ferritin and the dependent variable was prognosis of patients with acute attack of CHF. Univariate logistic regression analysis showed that alectin-3, RDW, Hepc, HS, and ferritin were protective factors for the prognosis of patients with acute attack of CHF. The independent variables were galectin-3, RDW, Hepc, HS and ferritin, dependent variables and the dependent variable was prognosis of patients with acute attack of CHF. Multivariate logistic regression analysis revealed that galectin-3, RDW, and Hepc were risk factors of the prognosis of patients with acute attack of CHF. Conclusion Galectin-3, RDW, Hepc, HS and ferritin were closely related with the prognosis of patients with acute attack of CHF and galectin-3, RDW, and Hepc were risk factors of the prognosis of patients with acute attack of CHF.